Climate Change and Integral Ecology - Sakimoto, Philip J (The Trumpeter, 2018)
Writing in his encyclical Laudato Si’: Care for Our Common Home, Pope Francis asserts that there is a “solid scientific consensus” on the reality of climate change and on its origins in human activities (#23). Unfortunately, much of the detailed scientific understanding that underlies this claim has not been made readily accessible to scholars in fields outside of the sciences. This paper aims to correct that omission by examining the science of climate change in the context of integral ecology. In this light, it will be demonstrated how human activities cause climate change, climate change has devastating effects on human lives and livelihoods, and human actions are necessary in order to mitigate climate change. Mitigating climate change requires societal actions that bring together technological, cultural, sociological, economic, and political considerations. The question is, do we have the wisdom to see that we are the cause of climate change, that climate change is rapidly making our planet unlivable for large numbers of human beings, and that we have to take strong and immediate actions if we are to avoid ever worsening future disasters? Hopefully, attention to integral ecology—to the interplay of human activities with natural ecosystems—can encourage us to do so.